2011
DOI: 10.4103/0028-3886.79139
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on chromosome 10q in glioblastomas, and its association with other genetic alterations and survival in Indian patients

Abstract: Assessment of promoter methylation of the O 6 -methylguanine DNA methyltransferase (MGMT) gene has recently gained importance in molecular profiling of high-grade gliomas. It has emerged not only as an important prognostic marker but also as a predictive marker for response to temozolomide in patients with newly diagnosed glioblastoma. Further, recent studies indicate that MGMT promoter methylation has strong prognostic relevance even in anaplastic (grade III) gliomas, irrespective of therapy (chemotherapy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Lower losses on chromosome 10 are seen in anaplastic astrocytoma indicating that loss of heterozygosity on chromosome 10 is a terminal genetic event associated with GBM [30]. Loss of heterozygosity on chromosome 10q has been found to be associated with reduced survival of GBM patients [9] and in a study of 25 cases of GBM in Indian patients was seen more frequently in older patients [31]. The loss of heterozygosity profile may thus have prognostic implications but to date has not guided treatment options.…”
Section: Molecular and Metabolic Alterations In Gbm And Their Potementioning
confidence: 99%
“…Lower losses on chromosome 10 are seen in anaplastic astrocytoma indicating that loss of heterozygosity on chromosome 10 is a terminal genetic event associated with GBM [30]. Loss of heterozygosity on chromosome 10q has been found to be associated with reduced survival of GBM patients [9] and in a study of 25 cases of GBM in Indian patients was seen more frequently in older patients [31]. The loss of heterozygosity profile may thus have prognostic implications but to date has not guided treatment options.…”
Section: Molecular and Metabolic Alterations In Gbm And Their Potementioning
confidence: 99%
“…The assessment of LOH10q genotype is not included in the recent WHO classification for gliomas (WHO 2016), as it is believed that the assessment of both chromosome 7+/10q− and TERTp mutations is perhaps more informative than assessing EGFR amplification for the diagnosis of GBM (7). Moreover, most studies to date have identified LOH of 10q as a poor prognostic marker for high-grade gliomas (8)(9)(10). Allelic deletion on chromosome 10q has also been observed in various advanced human malignancies (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%